The effect of lead exposure of mice during pregnancy on the concentration and motility of epididymal and testicular spermatozoa in offspring mature male mice - Al-Khfaji, Ina'am; Fakhrildin, Mohemed-Baqer; Al-Ani, Imad Matloub Dally; Mangalo, Hana'a; Al-Obaidi, Salim R. (Faculty of Medicine, International Islamic University Malaysia, 2011)
Introduction: The objective of this study was to investigate the effects of lead on concentration and motility of spermatozoa recovered from epididymis and testes in mature male offspring whose mothers were exposed to different doses and concentrations of lead acetate during gestation period. Materials and Methods: Seventy two healthy mature female mice were divided into three major groups according to the number of injections involving 1, 2 and 3 injections. Each major group was subdivided into four minor groups according to the concentration dose of (0, 25, 50 and 100) mg/Kg of lead acetate. Sperm concentration, percentage of motility and grade of activity were microscopically examined and statistically analyzed. Results: A significant reduction in the sperm functions were seen in relation to an increased in the number of injections and/or concentration of lead acetate dose as compared with the control groups. Conclusion: The toxic effects of lead acetate may interfere with spermatogenesis and metabolism of spermatozoa.